Pathological Cluster Identification by Unsupervised Analysis in 3,822 UK Biobank Cardiac MRIs - Zheng, Qiao; Delingette, Hervé; Fung, Kenneth; Petersen, Steffen E.; Ayache, Nicholas (Frontiers in Cardiovascular Medicine, 2020)
We perform unsupervised analysis of image-derived shape and motion features extracted from 3822 cardiac 4D MRIs of the UK Biobank. First, with a feature extraction method previously published based on deep learning models, we extract from each case 9 feature values characterizing both the cardiac shape and motion. Second, a feature selection is performed to remove highly correlated feature pairs. Third, clustering is carried out using a Gaussian mixture model on the selected features. After analysis, we identify two small clusters which probably correspond to two pathological categories. Further confirmation using a trained classification model and dimensionality reduction tools is carried out to support this discovery. Moreover, we examine the differences between the other large clusters and compare our measures with the ground-truth.